2016
DOI: 10.1007/s10661-016-5207-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of encroachment on wetlands: a case of Nakivubo wetland in Kampala, Uganda

Abstract: Wetlands provide vital ecosystem services such as water purification, flood control, and climate moderation among others, which enhance environmental quality, promote public health, and contribute to risk reduction. The biggest threat to wetlands is posed by human activities which transform wetlands, often for short-term consumptive benefits. This paper aimed to classify and map recent land cover and provide a multi-temporal analysis of changes from 2002 to 2014 in the Nakivubo wetland through which wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The reduction in size of the Anyiko wetland was, however, not only because of farmland expansion, but also encroachment of open and close shrublands by 15 and 2%, respectively. This finding is consistent with the study of Isunju and Kemp (2016), which reported a loss of Nakivubo wetland in Uganda by 2% between 2002 and 2014 because of encroachment by trees and shrubs (shrubland). Typically, wetlands are inhabited by flood tolerant vegetation (Cronk and Fennessy, 2016) and therefore encroachment by shrubland indicate drying out of some parts of the wetland.…”
Section: Discussion Land Use/cover Change In the Anyiko Wetlandsupporting
confidence: 93%
See 3 more Smart Citations
“…The reduction in size of the Anyiko wetland was, however, not only because of farmland expansion, but also encroachment of open and close shrublands by 15 and 2%, respectively. This finding is consistent with the study of Isunju and Kemp (2016), which reported a loss of Nakivubo wetland in Uganda by 2% between 2002 and 2014 because of encroachment by trees and shrubs (shrubland). Typically, wetlands are inhabited by flood tolerant vegetation (Cronk and Fennessy, 2016) and therefore encroachment by shrubland indicate drying out of some parts of the wetland.…”
Section: Discussion Land Use/cover Change In the Anyiko Wetlandsupporting
confidence: 93%
“…Loss of wetlands to agriculture in sub-Saharan Africa have also been reported by other studies. For example, Isunju and Kemp (2016) reported 62% of the wetland vegetation loss in Nakivubo wetland in Uganda, between 2002 and 2014, 30% of which was due to drainage and conversions to farmland. In addition, Troy et al (2007) reported 52% loss of Ga-Mampa wetland in South Africa between 1996 and 2004 to farmland.…”
Section: Discussion Land Use/cover Change In the Anyiko Wetlandmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Kampala Metropolitan Area (Uganda), the proportion of severely degraded wetlands increased from 13% in 1993 to 46% by 1999 (Nyakaana et al, 2007). In particular, Nakivubo wetlands experienced a 62% loss in wetland vegetation between 2002 and 2014, mainly due to crop cultivation (Isunju, 2016), despite their high estimated economic value of between US$ 760,000-1,300,000 (Schuijt, 2002). Similar observations have been made for the Nyanza Gulf in Kenya by Juma et al (2014).…”
Section: Relationships Between Land Use Changes and The Eutrophicatiomentioning
confidence: 99%